A Systematic Literature Review of Failure Mode and Effect Analysis (FMEA) Implementation in Industries - Zuniawan, Akhyar (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2020)
Failure mode and effects analysis (FMEA) is a risk assessment tool that mitigates potential failures in systems, processes, designs, or services and has been used in a wide range of industries. The conventional risk priority number (RPN) method has been criticized for having many shortcomings. Various risk priority models have been proposed in various literature to improve the performance of the FMEA itself. However, there has been no literature review on this topic. This study reviewed 50 FMEA papers published between 1998 and 2019 in international journals and categorized them according to various industry and industry output. The automotive and manufacturing industries dominated the implementation of FMEA. For the industry's production: goods and services, mostly dominated by interests in implementing FMEA in their industries. Hopefully, this finding will be useful for goods and services industries willing to implement FMEA, especially the services industry.